2023
DOI: 10.3390/insects14030275
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Analysis of Toll Receptor Genes during Antibacterial Immunity in the Green Peach Aphid Myzus persicae (Sulzer)

Abstract: The insect Toll receptor is one of the key members of the Toll signaling pathway, which plays an indispensable role in insect resistance to pathogen infection. Herein, we cloned and characterized five Toll receptor genes from Myzus persicae (Sulzer), which were found to be highly expressed in the first-instar nymphs and adults (both wingless and winged) at different developmental stages. Expressions of MpToll genes were highest in the head, followed by the epidermis. High transcription levels were also found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Various types of Toll genes have been identified in the genome of diverse insect orders, including Lepidoptera, Hymenoptera, Diptera, and Coleoptera (He et al 2023). Christophides et al (Christophides et al 2004) reported 10 specific Toll-related gene families associated with innate immunity in Anopheles gambiae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of Toll genes have been identified in the genome of diverse insect orders, including Lepidoptera, Hymenoptera, Diptera, and Coleoptera (He et al 2023). Christophides et al (Christophides et al 2004) reported 10 specific Toll-related gene families associated with innate immunity in Anopheles gambiae.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of Toll genes have been identified in the genome of diverse insect orders, including Lepidoptera, Hymenoptera, Diptera, and Coleoptera (He et al 2023). Christophides et al .…”
Section: Introductionmentioning
confidence: 99%